Cathode Pressure Control of Air Supply System for PEMFC⋆⁎Science and Technology Development Program of Jilin Province under Grant 20200501010G X, National Key Research and Development Program of China under Grant 2017YFB0102800. Issue 10 (2021) - Liu, Huayang; Yin, Hai; Ding, Tianwei; Huang, Xiaoliang; Gao, Jinwu
Abstract: This paper proposes a backstepping method controller for the polymer electrolyte membrane fuel cell (PEMFC)air supply system. The control objective is adjusting the cathode pressure to its reference value quickly, in order to solve the problem of excessive extreme pressure difference between anode and cathode in practice. Considering model uncertainty and some disturbances, we design an extend state observer (ESO) to estimate disturbances. Next, a backstepping method is proposed to adjust control law. Finally, the experiment results demonstrate the effectiveness and robustness of the control strategy.